Biodiversity and Species Change in the Arctic Ocean: A View Through the Lens of Nares Strait - Kalenitchenko, Dimitri; Joli, Nathalie; Potvin, Marianne; Tremblay, Jean-Éric; Lovejoy, Connie (Frontiers in Marine Science, 2019)
Nares Strait is the Northern most outflow gateway of the Arctic Ocean, with a direct connection to the remaining multi-year ice covered central Arctic Ocean. Nares Strait itself flows into the historically highly productive North Water Polynya (Pikialasorsuaq). Satellite data shows that Nares Strait ice is retreating earlier in the season. The early season surface chlorophyll signal, which was a characteristic of the North Water, has also moved north into Nares Strait. However, given the vast differences in the hydrography and physical oceanographic structure of the North Water and Nares Strait there is no a priori reason to assume that the species assemblages and overall productivity this region between Greenland and Canada will be maintained in the face of ongoing sea ice decline. The North Water’s high marine mammal and bird populations are dependent on seasonally persistent diatom dominated phytoplankton productivity, and although there have been several studies on North Water phytoplankton, virtually nothing is known about the communities in Nares Strait. Here we investigated the microbial eukaryotes, including phytoplankton in Nares Strait using high throughput amplicon sequencing. Samples were collected from Kennedy Channel below the northern ice edge of Nares Strait through the Kane Basin and into the northern limit of the North Water. The physical oceanographic structure and initial community rapidly changed between the faster flowing Kennedy Channel and the comparatively wider shallower Kane Basin. The community changes were evident in both the upper euphotic zone and the deeper aphotic zone. Heterotrophic taxa were found in the deeper waters along with ice algae that would have originated further to the north following release from the ice. Although there was a high proportion of pan-arctic species throughout, the Nares Strait system showed little in common with the Northern North Water station, suggesting a lack of connectivity. We surmise that a direct displacement of the rich North Water ecosystem is not likely to occur. Overall our study supported the notion that the microbial eukaryotic community, which supports ecosystem function and secondary productivity is shaped by a balance of historic and current processes, which differed by seascape.